The Impact of the Outbreak of Russia-Ukraine War on Commodity, Stock and Cryptocurrency Market s - Jacek Karasińki; Jan Zadrożny (Studia i Materiały)
Purpose: This paper analyzes the impact of the Russian invasion of Ukraine in February 2022 on returns of three groups of assets, i.e., commodities, stocks, and cryptocurrencies. Methodology: The study was conducted using the event study method which allows for quantifying the reaction of market participants to releases of various types of information. Findings: The cumulative abnormal returns (CARs) suggest a mostly positive effect of the conflict outbreak on returns of several commodities, especially precious metals. The obtained results suggest that in times of global crises, investors may consider precious metals as a safe haven. The study also indicates that on the event day the examined stock markets reacted negatively to information about the war, but to varying degrees. The Russian aggression against Ukraine did not affect the cryptocurrency markets in a statistically significant manner. Research limitations: The future studies related to the issue of the impact of Russian aggression against Ukraine on different markets may utilize larger research samples. They also may look for some factors affecting the reaction of markets to information related to the Russian military aggression, like the size of markets, trading volume, or geographical proximity, and economic dependence in the case of equity markets. Value: The study may provide some practical implications for both investors and regulators, especially in relation to the expected behavior of the markets and their informational efficiency in times of global crisis.